Community-Led Total Sanitation (CTLS) to Prevent Stunting among Toddlers in Indonesia - Dwi Fitri Ningsih; Muhammad Ikhtiar; Baharuddin, Alfina (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2021)
Background: Stunting is an emerging problem in Indonesia. Poor environmental sanitation conditions can cause environmental-based infectious diseases. Community-Led Total Sanitation (CTLS) program is one of the programs that can reduce stunting cases. The purpose of this study was to analyze the relationship between Community-Led Total Sanitation (CTLS) to prevent infectious diseases and the incidence of stunting in the Kanjilo Health Center Work Area, Gowa Regency in 2021. Method: This study is a cross-sectional study. The sampling technique used was purposive Sampling with a total of 88 children under five. Data analysis was performed by univariate, bivariate with chi-square test and multivariate analysis with logistic regression by SPSS 20.0 version. Results: The study showed that the factors found to be associated with the incidence of stunting were defecations habits (p-value = 0.025), Washing hands with Soap Behaviour (WHSB) (p-value = 0.033), and bacteriology in water (p-value = 0.000). Bacteriology in water is the factor that has the strongest influence on the incidence of stunting with an OR value of 17,041. Conclusion: Suggestions in this study are expected to the community to maintain personal hygiene and environmental sanitation in order to prevent the emergence of environmental-based diseases, especially infectious diseases that can cause stunting on children under five years old.